The Role of Transformational Leadership in Enhancing Islamic Educational Quality - Annasih, Sa'aduddin; Hariyadi, Ahmad; Aniqoh Shofwani, Siti; Adewale, Sulaimon (Pascasarjana IAIN Kudus, 2026)
Transformational leadership is a leadership style that emphasizes profound organizational change by motivating, inspiring, and empowering individuals to achieve shared goals. In the context of Islamic education, particularly at Madrasah Tsanawiyah (MTs) NU Kudus, transformational leadership is expected to improve the quality of education by enhancing the learning process, strengthening teacher professionalism, and encouraging more participatory school management. This study aims to analyze the implementation of transformational leadership at MTs NU Kudus and its impact on improving the quality of Islamic education. A quantitative approach with a cross-sectional survey design was used to collect data from 100 teachers and staff members across 15 madrasahs. The data were then analyzed using partial least squares–structural equation modeling (PLS-SEM). The results show that transformational leadership significantly and positively impacts the quality of Islamic education. School principals who apply transformational leadership by providing inspiration, motivation, individualized support, and value-based direction successfully improve instructional processes, strengthen teacher professionalism, and foster a more inclusive and collaborative school culture. The findings also suggest that leadership based on moderate Islamic values increases stakeholder engagement, including active participation from students and parents. In conclusion, this study recommends strengthening leadership development programs to support sustainable educational quality enhancement and asserts that transformational leadership is an effective strategy for driving institutional improvement in NU-based madrasahs.